FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PNEUMONIA KOMUNITI DI RSUD DR PIRNGADI KOTA MEDAN TAHUN 2020 - RINI SRI AGUSTI SIJABAT; SRI REZEKI ARBANINGSIH (LP2MTBM MAKARIOZ, 2021)
This study aims to determine the correlation between risk factors of CAP with the incidence of CAP patients at RSUD PirngadiMedan which was held from February 2020 to March 2020. This study used a analytic descriptive method with cross sectionaldesign with a questionnaire instrument with 44 samples were then analyzed using the chi-square test. Chi-Square test resultsshowed that there was a relationship between age and the incidence of CAP with a value of p = 0.042 (p <0.05). There is arelationship between smoking and the incidence of CAP with a value of p = 0.049 (p <0.05). There is a relationship betweenrisk factors for alcohol consumption with the incidence of CAP with a value of p = 0.038 (p <0.05). There is a relationshipbetween the density of residential homes with the incidence of CAP with a value of p = 0.049 (p <0.05). And there is arelationship between the history of comorbidities with the incidence of CAP with a value of p = 0.049 (p <0.05). There is arelationship between risk factors for age, smoking, alcoholism, density of residential homes, and comorbid conditions withthe incidence of CAP.